Comparison of the bond strength between a hybrid ceramic and a conventional adhesive vs one based on 10 MDP - Cascante Calderón, Marcelo (2022)
The constant evolution of dental ceramics has led to the appearance of hybrid ceramics or also called PICN. However, these new materials require new adhesives and cementation techniques. Materials and Methods: Five VITA ENAMIC blocks were sectioned into sheets (12 x 14 x 1.5 mm), and their surfaces were treated by acid etching and sandblasting (50 µ Al2O4), then randomly divided into two groups according to the type of adhesive: conventional adhesive group (GAC, n = 30) and universal adhesive group (GAU, n = 30). In addition to this, 60 microtubes were made with resin; each of them was cemented with the same cement, on each of the ceramic sheets. After this procedure, they were stored in water at 37ºC for 24 hours. Each microtube was then peeled off by micro-shearing. And the bond strength (RU) was measured in MPa. Statistical analysis was performed with a Student's t test. Statistical significance was 0.05 and confidence was 95%. Results: The RU of the universal adhesive (36.94 MPa) were higher than the conventional one (32.76 MPa). Student's t showed that there was a difference between the groups. p = 0.009 Conclusions: RU on hybrid ceramic was better when the universal adhesive was used. Attempting to use a conventional adhesive plus a previously applied silane did not result in an improvement in bond strengths.